AN INVESTIGATION REGARDING NUTRIENT FORAMEN OF THE RADIUS - Elif Toklu; Latif Sağlam; Osman Coşkun; Ahmet Ertaş; Özcan Gayretli (İstanbul Tıp Fakültesi Dergisi)
Objective: Arteries that provide nutrition to the long bones pass through openings called nutrient foramen (NF). The number of studies on NFs of the radius is quite scarce. Therefore, this study aimed to determine the presence, number, direction, and anatomical localization of NFs of the radius. Material and Method: A total of 133 dry adult human radii were investigated in this study. The presence, number, position, and direction of NFs of the radii were determined. The shortest distance of NF to the most proximal point of the radius (DPE), the transverse diameter of the radius at the level of the NF (TD), and the shortest distance of the NF to the most prominent point of the dorsal tubercle (DDT) were measured. Furthermore, the foraminal index (FI) was calculated. Result: A single NF was found in 130 (97.7%) bones, and 3 (2.3%) radii did not have NF. The NFs were most commonly on the anterior surface (80%, 104 bones) and middle 1/3 (78.5%, 102 bones) part of the bones. All NFs were towards the elbow. The DPE, TD, and DDT were meanly 82.72±11.4 mm, 129.99±15.41 mm, and 14.6±1.97 mm, respectively. The average FI was 35.6±4.64. Conclusion: This paper provides additional information, such as the distance of nutrient foramen to the dorsal tubercle. Our results may help clinicians during applications related to the NF of the radius.